Tracing the Concept of Good Citizens and Thai Civic Education in the Absolute Monarchy Era: Analyzing the Writings of Chaophraya Phrasadet Sunrentharathibodi (M.R. Pia Malakul) - kaewmano ่jaruwan (King Prajadhipok’s Institute Journal, 2021)
This research paper aims to trace the concept of good citizens and Thai civic education in the absolute monarchy era by analyzing seven pieces of literature by Chaophraya Phrasadet Sunrentharathibodi (M.R. Pia Malakul). The study was done using content analysis to find the key terms for interpretation concerning the context of the literature and society at that time. The study found that the concept of good citizens and civic education were not suddenly instituted in Thai society after general education was introduced to the public. The concept of good citizens arose from the practice of educational management to create “good people” with Buddhist morality, “gentlemen”, and finally “good citizens”, who respectively have different levels of relations with the state. The role of good citizens in the absolute monarchy era can be linked to the concepts of the modern state and the body politic, which focus on the hierarchy of government. Hence, the role of citizens in this era is positioned as the “energy” of the country who would give support, especially regarding the economy and resources, to the country. So, education management for citizens in this era focused on general education together with Buddhist ethical training and career training. It can be said that education provision for citizens in Thailand’s absolute monarchy era was “knowledge-virtue education”. Finally, the study revealed that having an understanding of good citizens cannot be achieved through study of citizens alone. It is necessary to understand the political regime holistically together with the roles and positions of other political actors to point out what the “good citizen” is.